Length Contraction with Speed Explained as a Relativistic Doppler Effect - SANDU, Constantin; BRASOVEANU, Dan (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this paper the authors show that the mechanism of length contraction is simple and can be explained by the wave feature of body micro-components. From this point of view, the length contraction with speed perceived by a fixed observer is a Doppler relativistic effect.